Shrine of the Bhomiya Maharaja within Suswani Mata Temple Complex - Temples of India Project Team (Jio Institute, 2024)
A side shrine of the Bhomiya Maharaja on the premises of the Suswani Mata Temple next to the sacred Kera tree. The Kera tree is believed to be the spot where Suswani Ma manifested herself and eventually stayed at the location of the present-day temple.